1997
DOI: 10.1094/phyto.1997.87.10.1000
|View full text |Cite
|
Sign up to set email alerts
|

Clonality in Sclerotinia sclerotiorum on Infected Cabbage in Eastern North Carolina

Abstract: Eighty-four isolates of Sclerotinia sclerotiorum from four cabbage production fields in North Carolina and 16 isolates from an experimental cabbage field plot in Louisiana were DNA-fingerprinted and tested for mycelial compatibility. In a comparison with 594 unique DNA fingerprints of S. sclerotiorum from Canadian canola, no fingerprints were shared among Canadian, North Carolina, and Louisiana populations. DNA fingerprints from the North Carolina sample were distinctive from those of the Canadian and Louisian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(123 citation statements)
references
References 18 publications
11
110
1
Order By: Relevance
“…Some highly similar isolates indicate dispersal across the 90 km between Leithfield and Rakaia, but no recent dispersal was evident between Takaka and the other populations. Similarly, in a study of S. sclerotiorum infecting cabbages in North Carolina, dispersal between fields 75 km apart was indicated by identical clones, whereas greater distances (e.g., between North Carolina and Canada) appeared to preclude dispersal (Cubeta et al 1997). In contrast, Canadian studies found identical clones over distances up to 2000 km (Kohn 1995).…”
Section: Discussionmentioning
confidence: 89%
“…Some highly similar isolates indicate dispersal across the 90 km between Leithfield and Rakaia, but no recent dispersal was evident between Takaka and the other populations. Similarly, in a study of S. sclerotiorum infecting cabbages in North Carolina, dispersal between fields 75 km apart was indicated by identical clones, whereas greater distances (e.g., between North Carolina and Canada) appeared to preclude dispersal (Cubeta et al 1997). In contrast, Canadian studies found identical clones over distances up to 2000 km (Kohn 1995).…”
Section: Discussionmentioning
confidence: 89%
“…For example, some S. sclerotiorum isolates from the USA belonged to the same MCG as isolates from Canada and Switzerland, while other isolates from the USA were in the same MCG as isolates from Argentina (Kull et al, 2004). Other reports indicated lack of common MCGs in S. sclerotiorum isolates from North Carolina and Canada or North Carolina and Louisiana (Cubeta et al, 1997), and Canada, China, and England (Li et al, 2008). This lack of common MCGs may result of specific selection of MCG genotypes, due to differences in their adaptability to environmental conditions (Atallah et al, 2004;Kull et al, 2004).…”
Section: Isolates Mcgsmentioning
confidence: 99%
“…Prior researches on S. sclerotiorum population structure, in areas where canola, sunflower, cabbage, and other crops are grown, have shown that this pathogen populations are mainly clonal (Kohli et al, 1992(Kohli et al, , 1995Anderson and Kohn, 1995;Cubeta et al, 1997;Kohli and Kohn, 1998;Carpenter et al, 1999;Hambleton et al, 2002), even though some recombination has been detected (Cubeta et al, 1997;Carbone and Kohn, 2001a), being more evident in subtropical populations than in temperate ones (Carbone et al 1999;Carbone and Kohn, 2001b;Atallah et al, 2004;Sexton and Howlett, 2004;Sexton et al, 2006;Mert-Türk et al, 2007;Gomes et al, 2011).…”
Section: Recombination Vs Clonal Reproductionmentioning
confidence: 99%